2016
DOI: 10.1136/bmjsem-2015-000087
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety in top-level male and female football players

Abstract: BackgroundScientific studies on the prevalence of mental health problems in elite athletes are rare, and most have had considerable methodological limitations, such as low response rate and heterogeneous samples.AimsTo evaluate the prevalence of depression and anxiety in top-level football players in comparison to the general population, and to analyse potential risk factors.MethodsPlayers of all first league (FL) and of four U-21 football teams in Switzerland were asked to answer a questionnaire on player's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
154
15
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(205 citation statements)
references
References 24 publications
24
154
15
12
Order By: Relevance
“…En los últimos años han aumentado los trabajos que muestran interés en el estudio de la relación entre factores psicológicos y rendimiento deportivo en el fútbol femenino, destacando aspectos como la dureza mental, la autoestima y el control de la ansiedad (Williams, 2017), la predicción de las orientaciones de meta sugiriendo acciones específicas del entrenador (Granero-Gallegos, Gómez-López, Abraldes y Baena-Extremera, 2015), o el estudio de indicadores de salud mental como la depresión y la ansiedad (Junge y Feddermann-Demont, 2016), o los estados de ánimo (Arroyo del Bosque, Irazusta y González-Rodríguez, 2016). Así, parece muy pertinente la sugerencia de Rutkowska y Bergier (2015) señalando que examinar el perfil psicológico de las jugadoras puede otorgar mucha información útil para mejorar los programas de entrenamiento, especialmente en entrenamiento mental y en jugadoras que se aproximan al nivel profesional, tal y como plantea Martín-García (2003).…”
Section: Palavras-chaveunclassified
“…En los últimos años han aumentado los trabajos que muestran interés en el estudio de la relación entre factores psicológicos y rendimiento deportivo en el fútbol femenino, destacando aspectos como la dureza mental, la autoestima y el control de la ansiedad (Williams, 2017), la predicción de las orientaciones de meta sugiriendo acciones específicas del entrenador (Granero-Gallegos, Gómez-López, Abraldes y Baena-Extremera, 2015), o el estudio de indicadores de salud mental como la depresión y la ansiedad (Junge y Feddermann-Demont, 2016), o los estados de ánimo (Arroyo del Bosque, Irazusta y González-Rodríguez, 2016). Así, parece muy pertinente la sugerencia de Rutkowska y Bergier (2015) señalando que examinar el perfil psicológico de las jugadoras puede otorgar mucha información útil para mejorar los programas de entrenamiento, especialmente en entrenamiento mental y en jugadoras que se aproximan al nivel profesional, tal y como plantea Martín-García (2003).…”
Section: Palavras-chaveunclassified
“…Importantly these studies have also identified the high prevalence of sports injuries, with reported rates of 20% (Junge & Feddermann-Demont, 2016) and 25% (Gulliver et al, 2015). High intensity training and a maladaptive thinking style, that results in even high achieving athletes habituating quickly to the euphoria of success, have also been linked to depression in sport (Mummery, 2005).…”
Section: General Risk Factorsmentioning
confidence: 98%
“…Sporting injuries have been repeatedly identified in association with symptoms of mental ill-health (Gulliver et al, 2015;Hill et al, 2016;Johnson, 1997;Rice et al, 2016) and especially in younger athletes (Junge & Feddermann-Demont, 2016). Importantly these studies have also identified the high prevalence of sports injuries, with reported rates of 20% (Junge & Feddermann-Demont, 2016) and 25% (Gulliver et al, 2015).…”
Section: General Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland, France, Norway, Spain, and Sweden, the prevalence of symptoms of CMD ranges from nearly 20% for distress and adverse alcohol use to 43% for anxiety/ depression [5]. In Switzerland, the prevalence of depression in elite male and female football was found to be similar to the general population, reaching nearly 8% for mild-to-moderate depression [6]. By contrast, to our knowledge, scientific evidence about symptoms of CMD among professional football referees is not available yet.…”
Section: Introductionmentioning
confidence: 97%